Analisis Kebebasan Artistik dalam Mendukung Children’s Well-Being pada Anak Usia Dini - Glisna Nayla Saskiani; Taopik Rahman; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This research evaluates the significance of artistic autonomy in promoting the holistic well-being of young learners during early childhood. By granting children the liberty to manifest their ideas, emotions, and imaginative faculties through diverse creative mediums, artistic freedom serves as a fundamental catalyst for their emotional, social, and psychological maturation within educational frameworks. Adopting a qualitative methodology centered on library research, this study synthesizes data from peer-reviewed journals and scholarly texts published over the past five years. The data acquisition process involved systematic literature retrieval utilizing specific descriptors such as "artistic freedom" and "children's well-being," followed by a rigorous content analysis. The results demonstrate that unrestricted artistic expression substantially improves emotional regulation, self-efficacy, and interpersonal competencies. Furthermore, the study highlights the teacher’s function as a facilitator who must cultivate an environment conducive to exploration without imposing creative constraints. Consequently, integrating artistic freedom into pedagogical strategies is recommended as a highly effective approach to enhancing well-being in early childhood education